2021
DOI: 10.1108/apjml-01-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Organizational citizenship behaviors perceived by collectivistic 50-and-older customers and medical-care service performance: an application of stimulus-organism-response theory

Abstract: PurposeThe study aims to examine the underexplored agenda in organizational citizenship behaviors (OCBs) through the collectivistic 50-and-older customers' lens when encountering medical-care services by applying stimulus-organism-response (S-O-R) theory.Design/methodology/approachThe authors propose an integrative causal model derived from employees OCBs perceived by the collectivistic 50-and-older outpatients in Korean medical-care organizations and test the causal relationships using structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 130 publications
1
3
0
Order By: Relevance
“…Second, this study sought to identify an indirect effect of life satisfaction on customer satisfaction through service-oriented OCB, and this was supported by the results. The mediating role of service-oriented OCB on the life satisfaction–customer satisfaction link resonates with previous research which found that life satisfaction can predict organizational citizenship behavior [ 17 ] through job satisfaction [ 16 , 18 ] and then predict customer service quality [ 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Second, this study sought to identify an indirect effect of life satisfaction on customer satisfaction through service-oriented OCB, and this was supported by the results. The mediating role of service-oriented OCB on the life satisfaction–customer satisfaction link resonates with previous research which found that life satisfaction can predict organizational citizenship behavior [ 17 ] through job satisfaction [ 16 , 18 ] and then predict customer service quality [ 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, organizational citizenship behavior is vital for promoting customer service quality [ 26 ]. For example, organizational citizenship behavior can improve customer satisfaction [ 27 , 28 ] and customer loyalty [ 72 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Favorable pre-core and core SE induce post-core, compliance with confirmation theory, which eventually creates value for patients. Accordingly, if service delivery provided by healthcare organizations meets patient expectations, satisfaction emerges, thus leads re-patronage and positive word-of-mouth intention (Kim et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulus-Organism-Response (SOR) Theory. According to (Kim et al, 2022), an external stimulus can affect the emotional perceptions of a person (organism), which in turn can lead to a response that can be either positive or negative behavior. According to this theory, when tourists get a stimulus from a high-quality destination it will encourage a sense of tourist satisfaction, resulting in positive behavior, namely the intention to revisit a destination.…”
Section: Theoretical Reviewmentioning
confidence: 99%